huis

16 Reputation

2 Badges

13 years, 73 days

MaplePrimes Activity


These are questions asked by huis

Hi! I have the following equation to solve: J1*K11-k*K1*J11=0 where: Jx=BesselJ(v,c*sqrt(a-x^2)) K11=BesselK(v+1,c*sqrt(x^2-b)) K1=BesselK(v,c*sqrt(x^2-b)) J11=BesselJ(v+1,c*sqrt(a-x^2)) k=sqrt(a-x^2)/sqrt(x^2-b) Any suggestion to find x???? I tried with "solve", but it says "Warning solutions may have been lost" Also tried with RootFinding --> Analytic, but after processing a while there is no output.. Any suggestion is very welcome!! thanks!
Page 1 of 1